PROSES PENGOLAHAN GARAM SECARA TRADISIONAL BERBASIS RAMAH LINGKUNGAN OLEH MASYARAKAT DI GAMPONG LANCANG PARU KECAMATAN BANDAR BARU KABUPATEN PIDIE JAYA - Mouliza, Mouliza; Armi, Armi; Azwir, Azwir (Jurnal Seramoe Education, 2025)
This research aims to (1) How the traditional salt processing process is carried out by the community in Gampong Lancang Paru (2) How the traditional salt processing method can be categorized as environmentally friendly (3) What are the challenges and benefits faced by the community in carrying out salt processing traditionally. This study uses a qualitative research method. The population in this study were all salt processing ponds in Gampong Lancang Paru, Bandar Baru District, Pidie Jaya Regency, namely 7 salt processing ponds, each consisting of 7 managers and 4 employees in each pond, the total number of employees is 28 employees. While the sample in this study was 1 salt processing pond in Gampong Lancang Paru consisting of 1 manager and 3 employees who work in the salt ponds in Gampong Lancang Paru. Data collection techniques were carried out by conducting Observations, Questionnaires and Interviews. The results of the study showed that the salt processing process began with filling seawater that was collected in a drilled well, then poured into a container to be cooked for 5 nights or even up to 2 weeks (14 days). While the salt processing method in Gampong Lancang Paru still maintains the traditional method for various reasons, one of which is environmental sustainability. The challenges and advantages faced by the community in carrying out traditional salt processing, the challenges faced are weather (climate) and limited human resources (HR). While the benefits of earning income, its importance in industry and sources of income.